Prediction of generalised and localised Carbon steel corrosion using improved Norsok and Papavinasam Models (2017)
In this study, Norsok and Papavinasam models have been improved so as to reduce the model limitations. The Norsok model was improved by accounting for 3 phase flow in calculating the wall shear stress and correcting for oil wetting and formation of protective layers in steel pipes during hydrocarbon transportation while the Papavinasam model was improved by using the Weibull distribution to account for time effect in corrosion predictions. The corrosion rates predicted fairly agreed with the field values. The improved models are user friendly and readily available and thus applicable for corrosion studies in the oil and gas industry.